Public Service Innovation: Drawing Inspiration from The Success of Developed Countries to Improve Public Services in Indonesia - Randini, Hilda Piska; Muslim, Muh. Azis (Publikasi Indonesia, 2024)
Innovation in public services has become inevitable and relevant in the development of modern society. The importance of this innovation lies in efforts to provide services that are more effective, efficient and responsive to the needs of the community, which are universal and contextual. Developed countries such as China, South Korea, and Denmark have become role models in developing public service innovation. They leverage technology, inclusive policies, community engagement, and approaches focused on user needs. Case studies of public service innovation in China, South Korea, and Denmark provide insight into the success of innovation in its public services. The results of this study show that there are several success factors that include the development of systems, procedures and methods, infrastructure, personnel training, and community empowerment so as to help the success of service innovation in the public sector that is more responsive, inclusive, and oriented to community needs.